A new DC–DC converter based on voltage‐lift technique. (16th September 2015) - Mohammadzadeh Shahir, Farzad; Babaei, Ebrahim; Sabahi, Mehran; Laali, Sara
Summary: In this paper, a new boost dc–dc converter based on voltage lift (VL) technique is proposed. There is any need for transformer, coupled inductances and sequential connections in the proposed boost converter topology. In this paper, the operating of proposed boost dc–dc converter in continuous conduction mode (CCM) and discontinuous conduction mode (DCM) was discussed, and the current and voltage equations of the inductors and capacitors were obtained with details. So, the value of critical inductance and the operating of the proposed dc–dc converter between CCM and DCM were presented. The switching currents of each switch were analyzed. The switches, diodes, inductors and capacitors root‐mean‐square (RMS) current stresses were discussed. Finally, the correct performance of the proposed converter based on presented theoretical issues is verified by using simulation results on EMTDC/PSCAD software program and experimental results by using laboratory prototype. Copyright © 2015 John Wiley & Sons, Ltd.